Council and school funding - Kate Ogden; David Phillips; Luke Sibieta (Institute for Fiscal Studies (IFS), 2023)
After health, funding for Scottish councils is the second largest item in the Scottish Government's Budget. In the original 2022-23 budget as passed by the Scottish Parliament, the Scottish Government allocated 10.6 billion to councils as part of the main local government portfolio, with further funding from other portfolios increasing the amount initially provided in the annual local government finance settlement for resource (i.e. non-capital) spending to 12.0 billion. The 2010s saw cuts to councils' funding and spending, but more recently funding has been increasing again. This chapter of the report therefore first looks at how Scottish councils' spending on local services changed during the 2010s, splitting spending into spending on schools and spending on other services to allow for easier comparisons of trends in England (although differences in data and responsibilities mean these comparisons are somewhat rougher for the 'other services' category). It then looks forward to 2023-24 and 2024-25, looking at the outlook for overall council funding including for schools, and how this compares with England.
Keywords: 330; Education and skills; Government finances and spending; Scottish Budget 2023-24; Scottish independence; Devolved government finances; Government spending; Education; Schools